RANCANG BANGUN SISTEM INFORMASI PENERIMAAN SISWA BARU BERBASIS WEB - iwan setiawan (Jurnal Komputer dan Teknologi, 2026)
This research is motivated by the need for schools to provide a more effective, efficient and accurate information system for new student admissions in order to overcome the obstacles of the conventional registration process which still uses paper forms and is prone to delays and data loss. The aim of the research is to design and build a web-based information system for new student admissions that can help schools manage registration data and make it easy for prospective students to obtain information. The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. The system development method applied is a prototype, allowing for gradual adjustments to user needs. The research results show that the information system built is capable of providing online registration features, printing proof of registration, reporting prospective student data, as well as easy access to information without having to come directly to school. This system minimizes administrative obstacles, increases the speed of service, and supports transparency in the process of admitting new students. The conclusion of this research is that a web-based information system can be the right solution to improve the quality of new student admission services at schools, and can be further developed by improving the interface and regular evaluation to suit user needs.